Ari, R U There? Reorienting Business Communication for a Technological Era - Reinsch, N. Lamar and Turner, Jeanine Warisse (Journal of Business and Technical Communication, 2006)
As technology changes business practices, it becomes even more important that our students—and we ourselves—think rhetorically. Our pedagogy should help students look at (not just through) new media to understand how new media reshape the rhetorical situation (audience, exigency, constraints) and to use them effectively. Furthermore, new digital technologies that capture and preserve business messages create opportunities and raise new research questions. Viewing business practices through the lens of rhetoric can provide a valuable perspective for research and emphasize the community-shaping aspects (and thus an ethical dimension) of business. Therefore, in this commentary, the authors call for a reorientation of the field of business communication.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDUwNjUxOTA2Mjg3MjU3